Penerapan Keterampilan Dasar Mengajar Dalam Pembelajaran Seni Budaya di Kelas Viii 2 SMP Negeri 14 Padang - Jauharul Anwar; Erfan Lubis; Yos Sudarman (FBS Universitas Negeri Padang, 2015)
Abstrak The formulatian of the research problem was “How was the teaching and learning process of Cultural Art (Music) conducted in class VIII-2 of SMP Negeri 14 Padang?” Based on this formulation, this research sought to explain the impelementation of basic skill of teaching and the teaching and learning process of Cultural Art (Music) conducted in class VIII-14 of SMP negeri 14 Padang. The theoretical review applied in this research was about teaching and learning process, the definition of teaching and learning process, the implementation of teaching and learning process, and teaching and learning process of music at scool. This was a qualitative research which applied descriftive analysis method. The result of the reserch revealed that the basic skill of teaching is very importand to conduct the teaching and learning process of music. This skill is closely related to the technical and non-technical ability of the teacher to conduct music teaching and learning process. There are eight teaching skills needed by the teachers to design the teaching and learning process, and the results could be seen in the learning activities in the classroom. Keywords: Studi Komparatif, Bernyanyi, Siswa, Notasi Angka.